Investigation of secondary phase separation and mechanical properties of epoxy SBS-modified asphalts. (20th March 2018) - Liu, Ya; Zhang, Jing; Jiang, Yongjia; Li, Chenxuan; Xi, Zhonghua; Cai, Jun; Xie, Hongfeng
Graphical abstract: Highlights: Epoxy SBS-modified asphalt (ESBA) has been developed. ESBA contains a secondary phase separation. ESBA provides extraordinary long mixing and compacting time for mixture pavement. The existence of SBS greatly improves the mechanical properties of the epoxy asphalt. Abstract: Styrene-butadiene-styrene triblock copolymer (SBS) and epoxy resin have been widely applied in asphalt modification. In the present work, industrial SBS-modified asphalt (SBA) was used to prepare epoxy SBS-modified asphalt (ESBA). The morphology, rheological, thermal and mechanical properties of ESBAs were characterized. LSCM observations revealed that the formation of phase-separated microstructures between epoxy and SBA in ESBAs. Secondary phase separation occurred in epoxy asphalts (EAs) with 50 and 60 wt% asphalts. The phase inversion occurred in epoxy asphalt with 60 wt% asphalt. In addition, the morphology of ESBAs also exhibited secondary phase separation. Two interlocked continuous phases appeared in SBA domains of ESBA with 40 wt% SBA. No phase inversion was observed in ESBA with 60 wt% SBA. The presence of SBS decreased the average size of dispersed domains in EA. The existence of SBS increased the initial viscosity of the epoxy asphalt during cure reaction. The viscosity of ESBA was low enough to satisfy the requirement for the pavement of steel bridge decks. The thermal stability of EA was enhanced with the existence of SBS. Furthermore, the presence of SBS significantly improved mechanical properties of the epoxy asphalt. Especially, the tensile strength, elongation at break and toughness of ESBA containing 60 wt% SBA were 125%, 55% and 113% higher than those of the epoxy asphalt with the same content of asphalt.